The synthesis and cyclotetramerisation reactions of aryloxy-, arylalkyloxy-substituted pyrazine-2,3-dicarbonitriles and spectroelectrochemical properties of octakis(hexyloxy)-pyrazinoporphyrazine - KOCA, ATIF (ELSEVIER SCI LTD, 2010)
Novel, aryloxy- and arylalkyloxy-substituted pyrazine dicarbonitriles were synthesized from 5,6-dichloropyrazine-2,3-dicarbonitrile and the corresponding phenol/alcohol derivatives. Cyclotetramerisation of these pyrazine derivatives to form metal pyrazinoporphyrazines in the presence of appropriate metal salts in different solvents such as DMF, quinoline, 2-dimethylaminoethanol and n-hexanol, resulted in decomposition products with the exception of tell latter solvent which lead to mainly octakis(alkyloxy) pyrazinoporphyrazines. Cyclic voltammetry and differential pulsed voltammetry of the complexes indicated that cobalt pyrazinoporphyrazine displayed both ligand and metal-based redox processes while zinc and copper derivatives exhibited only ligand-based redox processes. The redox processes of the pyrazinoporphyrazines shifted significantly towards positive potentials compared to those of the common phthalocyanines. The novel compounds were characterised using elemental analysis and spectral techniques. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Diaminomaleonitrile; Pyrazine dicarbonitrile; Cyclotetramerisation; Pyrazinoporphyrazine; Electrochemistry; Cobalt; ZINC PHTHALOCYANINE COMPLEXES; ELECTROCHEMICAL CHARACTERIZATION; OPTICAL-PROPERTIES; PHOTODYNAMIC ACTIVITY; METAL-COMPLEXES; AZAPHTHALOCYANINES; BEHAVIOR; 2,3-DICHLORO-5,6-DICYANOPYRAZINE; COBALT; TETRAPYRAZINOPORPHYRAZINES